PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PEMBELAJARAN PAPAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SD KELAS IV - Namira, Suffi; Anitra, Rien; Cinda Hendriana, Evinna (Jurnal keilmuan dan Kependidikan dasar, 2024)
The primary goals are as follows: 1) to compare the mathematical concept understanding of students taught using direct learning versus the TGT learning model with the help of PAPAR learning media; 2) to measure the impact of the TGT learning model with PAPAR learning media on students' mathematical concept understanding; and 3) to observe students' reactions after implementing the TGT learning model with PAPAR media on their mathematical concept understanding. A quantitative and experimental approach is used in this study. The research methodology for this study was a quasi-experimental design using a Nonequivalent Posttest Only Control type. Fourth graders from SDN 10 Singkawang participated in the research, which used a non-probability sampling approach based on a saturated sample. The results of this research show that: (1) compared to students whose math lessons used the direct learning model, those whose classes utilized the TGT learning model with the help of PAPAR learning media had a stronger grasp of mathematical ideas. While t_hitung is greater than t_tabel. The following are the reasons why: (1) We reject Ho and accept Ha; (2) The TGT learning model with the help of PAPAR learning media has a significant impact on students' ability to understand mathematical concepts; (3) The average response rate of 77% from students to the TGT learning model with the help of PAPAR learning media is very high.